Chromosomal Abnormalities 2020
DOI: 10.5772/intechopen.92859
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy in the Ginger Family from Thailand

Abstract: Polyploidy is common in the ginger family Zingiberaceae. The aims of the present paper are (1) to provide a general introduction on species diversity with emphasis on conservation; (2) to highlight the human-use significance of this family, focusing on the two major genera, Zingiber (ginger) and Curcuma (turmeric); (3) to present chromosome number data from 45 natural and cultivated Curcuma taxa from Thailand, of which polyploids are predominant; and (4) to describe our own work on cytotaxonomy of selected Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…Genomic polyploidy in members of Curcuma genus is well known from previously reported experimental studies 27,85,86 . In this study, we estimated the ploidy level of C. longa genome using next-generation sequencing (NGS) reads, and showed the triploid nature of C. longa genome, which is also supported by the previous experimental studies 27,28,85,86 . The application of Oxford Nanopore long-reads and 10x Genomics linked read sequencing that has the potential to resolve complex polyploid genomes 87 , helped in successfully constructing the C. longa draft genome of 1.02 Gbp with a decent N50 of 100.6 Kbp.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Genomic polyploidy in members of Curcuma genus is well known from previously reported experimental studies 27,85,86 . In this study, we estimated the ploidy level of C. longa genome using next-generation sequencing (NGS) reads, and showed the triploid nature of C. longa genome, which is also supported by the previous experimental studies 27,28,85,86 . The application of Oxford Nanopore long-reads and 10x Genomics linked read sequencing that has the potential to resolve complex polyploid genomes 87 , helped in successfully constructing the C. longa draft genome of 1.02 Gbp with a decent N50 of 100.6 Kbp.…”
Section: Discussionsupporting
confidence: 78%
“…According to the Plant DNA c-values database 25 , C. longa genome has an estimated size of 1.33 Gbp with 2n = 63 chromosomes, but a wide range of genome size variation (4C values ranging from 4.30 to 8.84 pg) and chromosome number variation (2n = 48 to 2n = 64) in C. longa was suggested 26 . Recent studies showed evidence for a ploidy level of 3X (2n = 63 chromosomes, basic chromosome number X = 21) 27,28 .…”
mentioning
confidence: 99%
“…The complex diversity of morphology, chromosome numbers and chromosome sizes in curcuma species indicates that these species have a unique evolutionary history in which polyploid events may play an important role ( Leong-Skornicková et al., 2007 ). Polyploidy is more common in the curcuma and zingiber genus ( Anamthawat-Jónsson and Umpunjun, 2020 ). We identified the polyploidy events in two sequenced Zingiberaceae species, which observed one recent WGD shared between turmeric and ginger.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger which shares the same family along with turmeric is known to have almost similar genome size which is about 1.5Gbp very near to turmeric and so known to have same growth and development cycle apart from medicinal and therapeutic properties. Different turmeric species are known to have changes in their diploid chromosome numbers [30]. India 42 Several turmeric cultivars belonging to same species differ in their diploid chromosome numbers depending the type of species which also effects their medical properties.…”
Section: Turmeric Genomementioning
confidence: 99%